EP1073 The prevalence of squamous intraepithelial lesions according to ethnic affiliation in Macedonia. (1st November 2019) - Dzikova, E; Dimitrov, G; Dimitrov, G; Tofoski, G; Daneva Markova, A; Djikova, E; Avramovska, M
Abstract : Introduction/Background: To determine the prevalence of abnormal Pap smears in different ethnic population in women from Macedonia. In our country, Pap smear test is included in the prevention program against cervical cancer to be performed every year in women aged 18 to 65. Methodology: We analyzed 1145 female patients, 129 with abnormal Pap smear and 1016 controls. The study was performed in 2015 in women aged 18–65, at the University Clinic for Gynecology and Obstetrics, Private General Hospital Re-Medika, Clinical Hospital 'Dr. Trifun Panovski' and in the Primary Health Institution 'Dr. Emilija Trajkovska'. Results: From 1145 analyzed female patients and 129 (11.3%) abnormal Pap smears, we found 9 patients (6.97%) with cell changes from viral infection, 50 (38, 76%) HPV positive patients on cytology test, CIN 1 in 34 patients (26.35%), CIN 2 in 9 patients (6.97%), ASC in 19 patients (14.72%), ASC-H in 6 patients (4.65%), and CIS in 2 patients (1.55%). Furthermore, from all Pap test positive patients, 15 patients had previous cervical conisation and following re-infection. The distribution of ethnicity among abnormal Pap smear women was as following: 107 (82.94%) were Macedonians, 12 Serbians (9.30%) with all types of cervical intraepithelial lesions, 5 Roma ethnicity (3.87%), 3 (2.32%) Albanians, 1(0.77%) Bosnian and 1(0.77%) Turkish ethnicity all with CIN1 lesion. Conclusion: Our study showed that the Macedonian population as the predominant population in Republic of Macedonia, was the most prevalent ethnicity with cervical intraepithelial lesions. Disclosure: Nothing to disclose